Extruded Unripe Plantain Flour as an Indigestible Carbohydrate-Rich Ingredient - Garcia-Valle, Daniel E.; Bello-Perez, Luis A.; Flores-Silva, Pamela C.; Agama-Acevedo, Edith; Tovar, Juscelino (Frontiers in Nutrition, 2019)
There is a growing interest in the development of functional ingredients, including those with high indigestible carbohydrate content. Unripe plantain flour (UPF) is a source of indigestible carbohydrates, type II resistant starch (RS) in particular. A major drawback of UPF, however, is that its RS content decreases sharply after wet heat treatment. Here, we explore the possibility of preparing an extruded UPF-based functional ingredient that retains limited starch digestibility features and high dietary fiber content. Both an unripe plantain pulp flour (UPFP) and a whole (pulp and peel) unripe plantain flour (UPFW) were prepared, extruded under identical conditions and evaluated for their gelatinization degree, total starch (TS), resistant starch (RS) and total dietary fiber (TDF) content; functional properties, such as pasting profile, water retention capacity and solubility, and oil absorption index were also analyzed. The extruded functional ingredient was added to a yogurt and the rheological characteristics and in vitro starch digestibility of the product were evaluated. The extruded UPFW showed a lower gelatinization degree than the extruded UPFP, which may be due to the higher non-starch polysaccharide content of the former. A high TDF content was recorded in both extrudates (12.4% in UPFP and 18.5% in UPFW), including a significant RS fraction. The water retention capacity and solubility indices were higher in the extruded flours, particularly in UPFW, while only marginal differences in oil retention capacity were observed among the products. The addition of UPFP or UPFW (1.5 g TDF, w/v) to a yogurt did not alter the viscosity of the product, an important characteristic for the consumer's approval. Moreover, the composite yogurt showed a relatively low starch digestion rate. Extrusion of unripe plantain flours may be an alternative for the production of functional ingredients with important DF contents.